Morphological systematics of Spathoglottis Blume (Orchidaceae: Collabieae) in Peninsular Malaysia and Borneo - Nordin, Farah Alia; Raffi, Akmal; Go, Rusea; Seok Yien Yong, Christina; Saibeh, Kartini; Othman, Ahmad Sofiman (Multidisciplinary Digital Publishing Institute, 2023)
Seventy-two morphological characters and three ecological characteristics were measured to assess variation and phylogenetic relationships among twelve species and three infraspecific taxa of the genus Spathoglottis from Peninsular Malaysia and Borneo. The morphological analyses divided Spathoglottis into two main groups based on the colours of the flower: Purple-Flowered Spathoglottis and Yellow-Flowered Spathoglottis. Species within the two groupings were further classified based on the size of the plants (Large/Dwarf Purple Spathoglottis and Large/Dwarf Yellow Spathoglottis) and the shapes of the labellum (spathulate, bilobulate or narrow/thread–like). The selected morphological characters appeared to support the taxonomic boundaries between two mostly debated taxa in the genus, S. aurea and S. microchilina.